PENERAPAN ASAS PACTA TERTIIS NEC NOCENT NEC PROSUNT BERKAITAN DENGAN STATUS HUKUM DAERAH DASAR LAUT SAMUDERA DALAM (SEA BED) - Aryuni Yuliatiningsih (Faculty of Law, Universitas Jenderal Soedirman, 2010)
International ocean seabed area out of national jurisdiction recognized as a common heritage of mankind. Its regulations under International authority based on UNCLOS 1982. UNCLOS 1982 didn’t universal acceptance because there are several states unwilling consent to be bound by a treaty. In the law of treaty there is pacta tertiis nec nocent nec prosunt principle, means a treaty does not either obligations or rights for a third State without its consent. Nevertheless, rules in a treaty becoming binding upon on third states through international custom and there is a principle has character erga omnesKey Words: pacta tertiis nec nocent nec prosunt principle, legal status, ocean seabed, erga omnes